INTERDISCIPLINARY ORTHODONTICS FOR IMPROVED DENTAL ESTHETICS IN THE FRONTAL AREA. A REVIEW - Loredana Golovcencu; Georgeta Zegan; Iulia Catalina Saveanu; Daniela Anistoroaei; Vasilica Toma (Romanian Dental Association for Education, 2019)
In the last decades orthodontics became part of an interdisciplinary dental team in order to contribute to the oral rehabilitation of the patients. In this paper we made a review of different clinical situations in which the necessity of an orthodontic stage was established by the general dentist in order to obtain better esthetic results in the anterior area. This particular situations refer to congenitally missing teeth, microdontia, peg-shaped lateral incisor , large diastema and abnormal axis of the anterior teeth which would make difficult the proper restauration of the frontal teeth.